Capacity development for resilient food systems: Issues, approaches, and knowledge gaps - Babu, Suresh Chandra; Blom, Sylvia (International Food Policy Research Institute, 2014)
Food systems face shocks varying in breadth and duration from a wide array of sources. These shocks can affect all aspects of a country’s food system, threatening the food security of its citizens. Low levels of capacity to address food system shocks are a major development challenge. This paper presents a conceptual framework for assessing the capacity of a food system to become more resilient, regardless of what kind of threat it faces. It suggests that food systems can be categorized into three subsystems: a policy system; markets, trade, and institutions; and a production system. Within each of these systems, three dimensions of capacity are analyzed: individual capacity, organizational capacity, and system capacity. The paper explores examples of building capacity within this framework and identifies key knowledge and research gaps. It also presents a typology as a possible tool for prioritizing investments in capacity building for resilience across countries.